The Influence of Family, Peer Group and Mass Media towards to Voting Behavior of FISIP UNDIP Studentâ€™s in the 2014 Presidential Election - Wicaksono, Andi Teguh; Astuti, Puji; Utomo, Susilo (Journal of Politic and Government Studies, 2015)
Studentâ€™s as â€œagents of changeâ€, in social life get a place as an elite thinker that has a function as a source of information, the source of knowledge, transfer of ideology, an indicator of national stability and political as well as agents of globalization, human rights enforcement, and democracy. The actions and activities taken by students canâ€™t be separated from the background of the state of economic, social, cultural, family and the environment in which it is located. Political socialization also had a role in shaping the character of a students. Political socialization raises individual attitudes such as: allowing individuals to vote whether or not to vote in elections. This research was intended to understand the extent of the influence of political socialization agentâ€™s that is: Family, Peer Group and Mass Media towards to Voting Behavior of FISIP UNDIP Studentâ€™s in the 2014 Presidential Electionâ€™s.This research uses quantitative explanatory methods. This research also studies in which the authors examine the verification is the causal relationship of the variables proposed. There are three independent variables (X), namely: the influence of family, peer group influence and the influence of the mass media to be searched influence on the dependent variable (Y) the voting behavior. Methods of data collection using the questionnaires poll then filled out by the respondent, namely FISIP UNDIP studentâ€™s many as 94 people. After data collected done then performed data analysis technique that is: multiple regression analysis, analysis of determination coefficient and hypothesis test using SPSS software.In the outcome of research found that the family, peer group and the mass media has an influence simultaneously or together 10.3% of the voting behavior of students FISIP UNDIP in the Presidential Election 2014. The influence of family, peer group and the media is positive so that if there is an increase will increase its influence on voting behavior of students FISIP UNDIP in the Presidential Election 2014. Variable families have a more significant influence than the variable peer group and mass media. Researchers are expected to further research can expand the scope of the object of study in order to obtain greater results, and can be used more and more results obtained could represent the situation of the actual conditions of society.